Estimating NOX, VOC, and CO variability over India’s 1st smart city: Bhubaneswar - Sahu, Saroj Kumar; Mangaraj, Poonam; Tyagi, Bhishma; Yadav, Ravi; Paul, Oscar; Chaulya, Sourav; Pradhan, Chinmay; Das, N.; Sahoo, Pallavi; Beig, Gufran (Frontiers in Environmental Science, 2022)
Volatile organic compounds including benzene, toluene, ethyl benzene, and xylene (BTEX) in the atmosphere have severe health and environmental implications. These variables are trace elements in the atmosphere. There are not enough measurement and analysis studies related to atmospheric BTEX variation globally, and studies are even less in developing countries like India. The present study analyses BTEX variations over an eastern Indian site, Bhubaneswar. The continuous measurement of BTEX is first of its kind over Bhubaneswar. The study analyses 2 years of BTEX data (2017–2018), and attempts to find the relation with meteorological parameters, the significance of the ratio between components, along with the analysis of transported air masses. To account for the pattern of emissions in association with BTEX variability over Bhubaneswar, we have also developed emission details from the transportation sector for the year 2018 and analyzed the emission patterns of CO and NOx for the year 2018. The results indicated that BTEX concentrations are maintained at the site via transportation from other regions, with significant local generation of BTEX, which is smaller in comparison to the transported emission.